RESPONSE OF THE ROOT-KNOT NEMATODE-INFECTED CELOSIA ARGENTEA TO BARK EXTRACTS OF KHAYA IVORENSIS - A., Fabiyi O.; A., Olatunji G.; O., Olagbenro M. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2017)
Plant parasitic nematodes are limiting factors in vegetable production. The most prevalent plant parasitic nematode on Celosia argentea is the root knot nematode Meloidogyne spp. Synthetic nematicide option of control brings about environmental pollution. The effect of dichloromethane and methanol extracts, in comparison with a standard synthetic nematicide (carbofuran) was studied on Meloidogyne incognita (Kofoid and White) Chitwood. 100g of extracts were dissolved in 200ml nonionic surfactant. Methanol extract (KAYV/MeOH) was significantly effective (p=0.05). Plant height, number of leaves and number of branches were significantly higher in KAYV/MeOH treated plants, while nematode population was lower. Spectroscopic results and phytochemical screening revealed the presence of secondary metabolites like aldehydes, phenols, alkyls, carbonyl and terpenes. Plant growth parameters are enhanced in this study by the metabolites, while the reduction in nematode population attested to the nematicidal effect of extracts from Khaya ivorensis.